3.36. Dany jest wzór funkcji kwadratowej f w postaci iloczynowej. Podaj wzór tej funkcji w postaci ogólnej. a) e) f(x) = – 1/4 * (x – 2) * (x + 10); f(x) = 3/5 * (x + 5) ^ 2; f(x) = – 2(x – sqrt(3)) * (x + sqrt(3)) b) d) f) f(x) = 8x * (x – 12); f(x) = – 5(x + 3) * (x – 8); f(x) = – (x – 4) * (x – 4)

 3.36. Dany jest wzór funkcji kwadratowej f w postaci iloczynowej. Podaj wzór tej funkcji w postaci ogólnej. a) e) f(x) = – 1/4 * (x – 2) * (x + 10); f(x) = 3/5 * (x + 5) ^ 2; f(x) = – 2(x – sqrt(3)) * (x + sqrt(3)) b) d) f) f(x) = 8x * (x – 12); f(x) = – 5(x + 3) * (x – 8); f(x) = – (x – 4) * (x – 4)